The dictatorship’s discourse: dictatorship, order and disorder in António de Oliveira Salazar - Guedes Pinto, Alexandra (2014)
In this study we focused on the analysis of the speech of António de Oliveira Salazar entitled ‘Administrative Dictatorship and Political Revolution’, delivered on the fourth anniversary of the Revolution of May 28, 1926, that ended the First Republic and implemented the New Regime of the Military Dictatorship in Portugal. This discourse works as an important milestone in the dictatorial regime legitimation process, where Salazar provides a justification for its implementation, while he defines a programmatic framework for its consolidation.In order to identify the linguistic mechanisms that underlie the legitimating force of the discourse and its power to (re)construct the reality, we analyzed the dominant semantic-axiological axes in the text, looking at how they are structured to present a dichotomous view of reality that favors a reconceptualized version of dictatorship: the dictatorship as a ‘National Salvation’ program.